2008
DOI: 10.7589/0090-3558-44.4.1051
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Studies on the Etiology of Keratoconjunctivitis in Reindeer (Rangifer tarandus tarandus) Calves in Alaska

Abstract: Keratoconjunctivitis outbreaks occur each summer in reindeer (Rangifer tarandus tarandus) herds in western Alaska, USA. This condition has not been well characterized nor has a definitive primary etiologic agent been identified. We evaluated the eyes of 660 calves near Nome, Alaska, between 29 June and 14 July 2005. Clinical signs of keratoconjunctivitis were observed in 26/660 calves (3.9%). Samples were collected from the conjunctival sac of both affected (n=22) and unaffected (n=24) animals for bacterial cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
2
7
0
Order By: Relevance
“…Although IKC in reindeer is reported to be caused by M. ovis (21), this bacterium may not be essential for the development of IKC in reindeer, as also indicated by a study from Alaska in which no such bacteria were found (13). We found that a Moraxella sp.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Although IKC in reindeer is reported to be caused by M. ovis (21), this bacterium may not be essential for the development of IKC in reindeer, as also indicated by a study from Alaska in which no such bacteria were found (13). We found that a Moraxella sp.…”
Section: Discussionsupporting
confidence: 51%
“…During an evaluation of 660 reindeer calves in western Alaska, where outbreaks of IKC in calves are reported to be common, clinical signs were found in 26 individuals. Since no primary viral or bacterial agent could be identified, a multifactorial cause was suggested, including the involvement of stress, ocular foreign bodies, and arthropods (13).…”
mentioning
confidence: 99%
“…This conclusion was supported by the fact that virus could be isolated from eye swab samples more frequently in animals with a mild stage of the disease, whereas in severe cases of IKC, only bacteria were recovered [15]. However, it remains unknown if the IKC frequently reported in Alaskan reindeer is related to a herpesvirus infection [16]. …”
Section: Introductionmentioning
confidence: 99%
“…In this case, they assumingly originate from the sampling team. Although papillomaviruses have been identified a few times in reindeer [4,37], not much knowledge exists on the etiology of papillomatosis in reindeer. The disease is observed from time to time, both in wild reindeer and semi-domesticated reindeer, although it is not considered as a common disease.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge on virus infections in caribou, and especially the WACH with its contact to reindeer herding on the Seward Peninsula, is crucial, because diseases may play a role in the declining population, and also because some viruses are expected to be transmitted between reindeer/caribou and other ruminant species. Few studies have been conducted to try to identify viruses in caribou through isolation, polymerase chain reaction (PCR), or metagenomic surveys [4]. Random amplification of nucleic acids and next-generation sequencing with metagenomics analyses has been successful in recent years in identifying new viruses from wild animals [5][6][7].…”
Section: Introductionmentioning
confidence: 99%